قضايا نقدية فی الادب العربی عند الشيخ أبي الحسن علي الندوي: Criticism in Arabic literature: A Study of the Views of Abu-ul-Hassan Alī al-Nadawī (Al-Qamar, 2019)
Along with huge contributions in the field of Islamic religious literature, scholars of Indo-Pak Sub-continent have been playing a pivotal role in serving and spreading Arabic language and literature. Abu-ul-Hassan Alī al-Nadawī is amongst the most prominent scholars of this line of action. This article studies Nadawī’s efforts for promotion and service of Arabic prose. It highlights several aspects of his critical views on the subject. It concludes that Nadawī has a remarkable critical approach in the field of Arabic language and literature. His efforts in the relevant field are not only appreciated by the scholars of Indo-Pak Subcontinent but also by the Arab scholars and writers.
Keywords: Abu-ul-Hassan Alī al-Nadawī; Arabic prose; Criticism